Epidemiology and potential risk factors of drug‐related problems in Hong Kong paediatric wards. (May 2014) - Rashed, Asia N.; Wilton, Lynda; Lo, Charles C. H.; Kwong, Benjamin Y. S.; Leung, Suzanne; Wong, Ian C. K.
<x xml:space="preserve">Abstract</x> Aims A drug‐related problem (DRP) is 'an event or circumstance involving drug therapy that actually or potentially interferes with the desired health outcome'. The extent and characteristics of DRPs in children in Hong Kong are unknown. The aim of this study was to determine the epidemiology of and identify risk factors for DRPs in hospitalized children in Hong Kong. Methods This was a prospective cohort study in children aged 0–18 years who were admitted to a medical ward, paediatric intensive care unit or neonatal intensive care unit of seven Hong Kong hospitals, during a 3 month period. Patients' charts, medical records and laboratory data were reviewed daily to identify DRPs; their preventability and severity were assessed. Logistic regression was used to analyse potential risk factors associated with the incidence of DRPs. Results Three hundred and twenty‐nine children (median age, 2 years; interquartile range, 0 months to 9 years) were included. In total, 82 DRPs were experienced by 69 patients. The overall incidence of DRPs was 21.0% (95% confidence interval, 16.7–25.8%). The incidence was higher in neonatal and paediatric intensive care units than medical wards. Dosing problems were the most frequently reported DRPs (n = 35; 42.7%), followed by drug choice problems (n = 19; 23.2%) and adverse drug reactions (n = 11; 13.4%). Sixty‐seven (81.7%) DRP cases were assessed as preventable, 42 (51.2%) as minor and 40 (48.8%) as moderate. The number of prescribed drugs and 'certain infectious and parasitic diseases' were potential risk factors for occurrence of DRPs. Conclusions Drug‐related problems were common in hospitalized children in this study in Hong Kong; the most frequent were dosing and drug choice problems, and the majority of them were preventable. Polypharmacy and 'certain infectious and parasitic diseases' were potential risk factors.